Sleep Quality in Normal Weight and Overweight Individuals: A Cross-Sectional Survey - Asghar, Muhammad Sohaib; Hassan, Maira; Akbani, Sarah Kamran; Shaikh, Nimra; Rasheed, Uzma; Akram, Mohammed; Ahmed, Nisar; Ahmed, Shahzad; Zafar, Talha; Saleem, Muhammad (Archives of Clinical and Biomedical Research, 2020)
Sleep is an important part of one’s daily routine and sleeping less than 6 hours at night is considered decreased somnolence. The frequency of obesity is shooting up worldwide, mainly in developed countries. Obesity has become a very grave root cause of health issues in our society. Our study aims to find out the association between obesity and sleep, and the frequency of poor sleep quality among normal weight-bearing and overweight individuals. It was conducted as a cross-sectional, observational, questionnaire-based survey, a total of 380 subjects were randomly selected from the community. Sleep quality was compared among both the groups using standard validated scale questionnaire for sleep quality (Pittsburg Sleep Quality Index). Our study found out that out of 380 individuals who were being inquired 228 (60%) individuals were normal weight-bearing and 68 (30%) were overweight. Sleep quality was found to be impaired in 120 (52%) of normal-weight individuals as compared to 36 (45%) overweight individuals, although mean PSQI was higher in overweight’s (p=0.008). We further found that self-reported sleep duration was not different in normal as well as overweight individuals. The rate of poor sleep quality was found equal among male and female overweight individuals. It is concluded that sleep quality is dependent on various factors including sleep awareness, sleep hygiene, environment, and other factors that should be taken into account also regardless of the weight of the person. We also recommend that working on awareness regarding the importance of sleep and helping parents to establish an appropriate sleep routine for young children may be useful in preventing obesity.